KNOWLEDGE AND BLOOD SUGAR LEVELS AMONG DIABETES MELLITUS PATIENTS IN THE HOSPITAL - Luluk Dermawan; Dwi Puji Susanti; Edy Soesanto ((IJP) Indonesia Jurnal Perawat, 2026)
Diabetes mellitus is a group of diseases related to the body's metabolism, characterized by excessively high blood sugar levels. Knowledge about diabetes mellitus is important because it helps people understand the disease. If respondents have insufficient knowledge about diabetes mellitus, they may not routinely check their blood sugar. This study aimed to analyze the relationship between knowledge and blood sugar levels in diabetes mellitus patients at the hospital. This research method used a correlational analytical research design with a cross-sectional approach. This study was conducted from October to November 2025 at the Pati Islamic Hospital. The population of diabetes mellitus respondents was 92, and a sample of 68 was selected using purposive sampling. Inclusion criteria included diabetes mellitus patients at Pati Islamic Hospital who were present when questionnaires were distributed and willing to participate. The exclusion criteria were patients with cognitive impairment or dementia and patients on exclusive insulin therapy. The independent variable is knowledge level, and the dependent variable is blood sugar level. Knowledge level was measured using the DKQ-24 (Diabetes Knowledge Questionnaire), and blood sugar was measured using an EasyTouch glucometer. Data analysis used the chi-square test. The results showed a p-value of 0.000. Therefore, there is a relationship between knowledge level and blood sugar in diabetes mellitus patients in the hospital. Conclusion: There is a relationship between knowledge level and blood sugar in diabetes mellitus patients in the hospital. Suggestion: It is hoped that respondents will increase their understanding by seeking information about diabetes mellitus and the factors that influence blood sugar levels.